VD_FINDINFO Décision / 2011 / 557 vom 6. Juli 2011 - VD Tribunal cantonal (2011)
TENTATIVEDROIT PÉNAL, MEURTRE, FIXATION DE LA PEINE | 111 CP, 22 al. 1 CP, 47 CP, 398 al. 3 let. a CPP (CH), 399 al. 4 CPP (CH)